Understanding Methodology of Fiqh Sosial - Umdatul Baroroh (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
This article aims at developing the methodology of fiqh sosial by exploring the concept of fiqh sosial that Kiai Sahal thought. It is very important to do this research. The research used the qualitative method. I conducted this research through a literature study by exploring Kiai Sahal's writings as a primary source and analyzing them by collaborating with observations on social movements that he had carried out during his life. The results of the analysis and observations become the main ingredients in building a fiqh sosial methodology. Next is combining the data with fiqh methodology and social knowledge, sciences, technology, and other modern sciences. That is important because fiqh sosial must be able to produce the Islamic law that can able to realize the benefit of mankind and contextual wherever and whenever it be. Since the ideas of fiqh sosial have been published by Kiai Sahal, a lot of researchers and academics have written the theme. But of all the writings that already exist, almost no one has written about its methodology. If found, it is still very shallow and inadequate.